Pemikiran Ulama Kontemporer Tentang Distribusi Dalam Islam: Riview Literatur Kualitatif - Mulki Akhdan; Mohd Winario; Rifqil Khairi (Journal of Economic, Management, Business, Accounting Sustainability, 2026)
Unequal distribution of wealth is a major problem in the modern economic system, contributing to increasing poverty and social injustice, including in Muslim societies. This situation emphasizes the urgency of examining the concept of distribution in Islamic economics as an alternative to a just economic system. This study aims to analyze the thoughts of contemporary Islamic scholars on distribution in Islam based on a qualitative literature review. The research method used is a qualitative approach using a literature review technique of the works of contemporary Islamic scholars and relevant scientific literature, analyzed using content analysis. The results indicate that contemporary Islamic scholars view distribution as a fundamental element of the Islamic economic system, oriented towards social justice and the welfare of the people. Distribution is implemented through the instruments of zakat (alms), infaq (donation), sadaqah (charity), waqf (endowment), inheritance systems, and the prohibition of exploitative economic practices, with the support of the state and society. This study recommends strengthening Islamic distribution institutions, optimizing the role of the state, and developing economic policies based on the maqāṣid al-shari'ah (objectives of the principles of sharia) so that the Islamic concept of distribution can be implemented effectively and relevantly in facing contemporary economic challenges.